AB0625 Emergency room Visits as a Risk Factor for Patients with Systemic Lupus Erythematosus: A Four-Year Retrospective Study in Japan. (9th June 2015) - Nagai, Y.; Yokogawa, N.; Shimada, K.; Sugii, S.
Abstract : Background: Many systemic lupus erythematosus (SLE) patients require emergency room (ER) visits because of flares and other complications. Distinguishing between flares and complications such as infections in the emergency ward is crucial to timely implementation of the required treatment, but sometimes poses a challenge for primary care and emergency physicians alike, resulting in delays in diagnosis and intervention. Objectives: The aim of this study is to describe the characteristics of SLE patients who visit the ER, and to determine the proportion of ER visits due to SLE flares with the ultimate aim of detecting the risk factors for ER visits using multivariate logistic analysis. Methods: A four-year retrospective study was performed at Tokyo Metropolitan Tama Medical Center using patients' electronic medical records. All records of emergency room visits by SLE patients from April, 2008 to March, 2012 were extracted from the data. Results: In total, 269 events were identified in 117 patients. Of these events, 91 (33.8%) were cases of infection, 32 (11.9%) of orthopedic problems and gastrointestinal disease, 31 (11.5%) of neurological disease, and 25 (9.3%) of cardiovascular events. Twenty four events (8.9%) were due to SLE flares, of which 10 (41.7%) were cases of neuropsychiatric lupus including disturbances in consciousness, aseptic meningitis, seizure, and visual field abnormality. The "ER user group" and "ER non-user group" comprised 117 and 88 patients, respectively. The dosage of glucocorticoids (prednisolone equivalent, 9.09±0.63mg, 5.36±0.73mg), intervention by psychiatrists (17/117 (14.5%), 3/88 (3.4%)), presence of neuropsychiatric lupus (23/117 (19.7%), 6/88 (6.8%)) and presence of lupus nephritis (48/117 (41.2%), 22/88 (25.0%)) were higher among the ER user group than the ER non-user group (p<0.05). As a result of multivariate logistic analysis, higher glucocorticoid dosage, duration of disease, and neuropsychiatric lupus were found to be risk factors for ER visits. Conclusions: Among SLE patients, infection was the principal reason for visiting the emergency room. ER visits due to SLE flares comprised only 8.9% of the total. Multivariate logistic analysis demonstrated that higher glucocorticoid dosage, duration of disease, and neuropsychiatric lupus comprised risk factors for ER visits. Disclosure of Interest: None declared